Role of reactive gas on the structure and properties of titanium nitride films grown by plasma enhanced atomic layer deposition - Krylov, Igor (2018)
The authors report on the role of various reactive gases on the structure and properties of TiN thin films prepared by plasma enhanced atomic layer deposition (PEALD) from tetrakis(dimethylamido)titanium. The reactive gas plays an important role determining the film structure and properties. Nitrogen-based plasma (N-2 and NH3) resulted in low oxygen (∼3%) and carbon (∼2%) contamination and well-defined columnar grain structure. A nitrogen excess (∼4%) was found in the films deposited using N2 plasma. The stoichiometric films and lowest resistivity (∼80 μΩ cm) were achieved using NH3 plasma. Deposition using H2 plasma resulted in higher carbon and oxygen contamination (∼6% for each element). The reactive gas also plays an important role in determining the grain size and preferential orientation. By varying the plasma chemistry, either (111) or (100) oriented films can be obtained. A mechanism determining the PEALD TiN preferential orientation is proposed. Finally, plasma induced degradation of the underlying dielectric layer is evaluated.